LINKING SUSTAINABILITY PERFORMANCE TO STOCK RESILIENCE DURING AND AFTER COVID-19 CRISIS: EVIDENCE FROM SOUTHEAST ASIA - Rahman, Khalilul; Retnosari, Retnosari; Komalasari, Sanda Patrisia; Wafiq, Muhammad (Jurnal Akuntansi dan Keuangan Indonesia, 2026)
Background: The COVID-19 pandemic severely disrupted markets. While sustainability performance measured by ESG scores theoretically buffers against shocks, its efficacy in emerging markets with nascent sustainability frameworks remains underexplored. Method: We analyze a balanced panel of 1,395 observations from 279 non-financial Southeast Asian firms (2020–2024). Using OLS, lagged, and fixed effects models, we compare the impact of sustainability performance on stock resilience during the 2020–2022 and post-pandemic (2023–2024) periods. Findings: Sustainability performance (ESG scores) significantly enhanced stock resilience during the pandemic. However, this protective effect dissipated post-pandemic. Results confirm a statistically significant improvement in overall resilience following the crisis, as investors redirected their focus toward traditional financial fundamentals such as profitability and leverage. Conclusion: Sustainability performance acts as situational crisis insurance. Its risk-mitigation value is highly salient during systemic uncertainty but diminishes under stable market conditions. Novelty/Originality of this article: Unlike prior single-phase studies in developed economies, this research provides longitudinal evidence on the dynamic, state-dependent nature of sustainability performance across crisis and recovery phases within Southeast Asia’s early-stage ESG landscape.